Control interno del capital de trabajo en las PYMES del sector pesquero - Arguello Castillo, Omar Eusebio (2022)
This research work focuses on the analysis of the internal control of the working capital of SMEs in the fishing sector of the Province of Santa Elena. Generally, companies that have adequate working capital management take advantage of several benefits such as: staying on over time, greater competitiveness among SMEs in the sector, and achieving established objectives. The proper management of working capital is of real importance for proper liquidity management of SMEs in the fishing sector because it is about managing current assets, current liabilities and being able to meet short-term obligations. This research is divided as follows:.........